Karakteristik Kombucha Dengan Penambahan Kulit Jeruk Siam Kintamani (Citrus nobilis L.) Pada Fermentasi Lanjutan - Wijaya, Kadek Ramana Sathya Pavana; Hapsari Arihantana, Ni Made Indri; Wisaniyasa, Ni Wayan (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Kombucha is a fermented beverage made from sweet tea using a symbiotic culture of bacteria and yeast (SCOBY) that has a sour taste and distinctive aroma but is not liked by some consumers. One effort to improve the sensory quality of kombucha is to conduct further fermentation with the addition of natural ingredients. This study aims to investigate the effect of adding kintamani siamese orange peel (Citrus nobilis L.) on further fermentation and to determine the optimal concentration of kintamani siamese orange peel for producing kombucha with the best characteristics. The experimental design used was a Completely Randomized Design with five treatments of siamese orange peel concentration additions: 0%, 1.5%, 3%, 4.5%, and 6%, repeated three times, resulting in 15 experimental units. The parameters observed included total acidity, pH, alcohol content, total dissolved solids, total sugar, antioxidant activity, hedonic evaluation, and sensory scoring. The results showed that the addition of kintamani siamese orange peel significantly affected total acidity, pH, total alcohol, total dissolved solids, antioxidant activity, and total sugar. The best treatment was obtained with the addition of 1.5% kintamani siamese orange peel, resulting in kombucha with total acidity of 2%, pH of 3.2, total alcohol of 0%, total dissolved solids of 8.5°Brix, antioxidant activity of 50.93%, and total sugar of 4.90%, with a color liked, slightly strong and liked aroma of kintamani siamese orange peel, slightly strong and liked taste of kintamani siamese orange peel, and overall preferred acceptance.